Effect of HPP treatment on the safety and quality of beef steak intended for sous vide cooking. (December 2017) - Sun, Shengqian; Sullivan, Gary; Stratton, Jayne; Bower, Chad; Cavender, George
Abstract: High Pressure Processing (HPP), a non-thermal microbial inactivation technology, can be potentially used as hurdle during processing while enhancing the taste and nutrition of muscle foods. In this study, the effect of HPP treatment on safety and quality of beef steak intended for sous vide cooking was determined. Beef steaks were inoculated with E. coli 0157:H7 via pin pad and then seared, vacuum packaged, and subjected to HPP. HPP treatment at 450 MPa for 15 min resulted in reductions of 4.74 log CFU/g in E. coli . At 600 MPa, E. coli levels saw reductions of 6.13 log CFU/g, after 10 min. HPP can achieve microbial reductions of E. coli exceeding the 5-log definition of pasteurization, allowing the potential for the creation of convenience products with reduced potential risk in home sous vides cooking. HPP treatment at 450 MPa and 600 MPa did not significantly change the properties of most seared beef steaks in term of pH, water activity, moisture content, expressible moisture. Additionally, while the degree of lipid oxidation (via TBARs) decreased significantly ( p < 0.05) in Post-HPP samples after sous vide cooking for 2 h, there was not significant difference among pressure treatment ( p > 0.05). Highlights: Sous Vide and High Pressure processing can be combined together to produce safe, potentially acceptable meat products. Key qualities of seared steaks (color, moisture content, and expressible moisture) were not significantly influenced by HPP. Sous vide cooking high pressure treated steaks did not alter the quality of the steaks, except in the most severely processed samples.